Numerical Simulation Study on Construction Effect of Top-Down Construction Method of Suspended Diaphragm Wall for Deep and Large Foundation Pit in Complex Stratum. (7th March 2022) - Zhu, Yunhui; Sun, Fuxue; Liu, Mingqing; Liu, Qifeng; Li, Xiaochun; Ge, Gang
Abstract : In order to study the deformation of a diaphragm wall and the settlement of surrounding soil under the complicated conditions of the deep and soft soil layer, which is underlying inclined rock and top-down construction method, the construction scheme of suspended diaphragm wall based on the engineering practice of Oujiang North Estuary deep and large foundation pit of Wenzhou S2 railway is proposed, and the research method of numerical simulation is adopted in this article. By using Midas GTS finite element software, a three-dimensional model of deep and large foundation pit excavation with top-down construction method is established, and the internal force, deformation, and surface settlement of surrounding soil of suspended diaphragm wall with different depths into rock (1 m, 2 m, and 4 m) are analyzed. Furthermore, the optimization simulation research on the anchor locking scheme is carried out for the determined footed diaphragm wall. Similarly, the anchor locking scheme at a depth of 1 m into the interface between soil and rock is selected as the supporting scheme of the footed diaphragm wall through the simulation results. The research results of this article can guarantee the safety of diaphragm wall construction of deep and large foundation pit in complex stratum.